Case Studies ofEmerging Ethnocentric Charter Schools in Hawai'i - Nina K Buchanan; Robert A. Fox (Arizona State University, 2003)
The fast growing charter school movement may be impeded if charter schools are perceived as a vehicle for stratifying, segregating, and balkanizing an already ethnically, socio-economically divided population. This article defines ethnocentric schools and describes three Native Hawai'ian charter schools. While they are very different in curricula and in emphasis on the Hawai'ian language and other features, they all have strong community support and a high degree of parental involvement and have access to funds available only for Native Hawai'ian programs. It may be easy to support the expenditure of public funds for ethnocentric charter schools in areas like Hawai'i where ethnic minorities have traditionally been underserved. The issues raised in this study may have broader implications for the evolution of American public education. The question is not what criteria to apply to distinguish schools of "good" choice from schools of "bad" choice. In final analysis we must ask, are schools of choice truly schools of choice, or not?